Confirmation of genetic heterogeneity in familial psoriasis. Issue 7 (July 1995) - Matthews, D; Fry, L; Powles, A; Weissenbach, J; Williamson, R
Abstract : Psoriasis affects approximately 2% of the European population and is often familial. Linkage of a subset of psoriasis families to loci on chromosome 17q has recently been reported. We have studied members of a large multiply affected family from the north east of England and analysed genotypes for markers from 17q, including the polymorphic microsatellite markers AFM210xa5, AFM163yg1, AFM044xg3, AFMa353yg1, and AFM217yd19. Two point and multipoint analysis clearly show exclusion of linkage between the telomeric region of 17q and psoriasis in this family. This confirms the genetic heterogeneity of psoriasis and the existence of at least one other major psoriasis locus.